1999
DOI: 10.1136/hrt.81.1.94
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate shocks delivered by implantable cardiac defibrillators during oversensing of activity of diaphagmatic muscle

Abstract: Two cases are reported (both men, one 72 and one 54 years old) of inappropriate shocks delivered by an implantable cardiac defibrillator (ICD) device, which oversensed the myopotentials induced by deep breathing and Valsalva manoeuvre. No damage to leads was associated with the oversensing of myopotentials. The mechanism of the inappropriate shocks was determined using real time electrograms. Modification of the duration of ventricular detection and decrease in sensitivity made it possible to avoid the oversen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0
1

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 8 publications
1
14
0
1
Order By: Relevance
“…Inappropriate ICD shock is also associated with oversensing of myopotential. Babuty et al reported the occurrence of inappropriate ICD shock due to the oversensing of diaphragmatic myopotential, with integrated bipolar sensing during deep breathing or the Valsalva maneuver, in the absence of lead damages or electrical interference [11]. The incidence of inappropriate detections due to the oversensing of diaphragmatic myopotential was reported to be 8.6%, whereas that of inappropriate ICD shocks was 3% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Inappropriate ICD shock is also associated with oversensing of myopotential. Babuty et al reported the occurrence of inappropriate ICD shock due to the oversensing of diaphragmatic myopotential, with integrated bipolar sensing during deep breathing or the Valsalva maneuver, in the absence of lead damages or electrical interference [11]. The incidence of inappropriate detections due to the oversensing of diaphragmatic myopotential was reported to be 8.6%, whereas that of inappropriate ICD shocks was 3% [12].…”
Section: Discussionmentioning
confidence: 99%
“…Bizim olgumuzda tremorun neden olduğu yüksek frekanslı ve güçlü kas kasılmaları ICD tarafından R dalgası olarak algılanmış ve şok vermesine neden olmuştu. Barakpour ve arkadaşları bir cisim fırlat-manın neden olduğu kas kontraksiyonları sırasında görü-len, Babuty ve arkadaşları ise diyafram kasılmaları sonucu gelişen miyopotansiyellere bağlı uygunsuz ICD şoku olguları bildirmişlerdir (8,9) . Miyopotansiyeller genellikle düşük amplitüdlü ve kısa süreli artefaktlara neden olmaktadır.…”
Section: Discussionunclassified
“…Late report of death prevented any possibility of lead extraction to determine the exact site of the isolation break. Oversensing is possible without structural lead failure, 4 , 13,14 but this phenomenon must lead to the search for an insulation defect, particularly in the case of inappropriate shocks 1 . To make an early diagnosis of this malfunction, noninvasive parameters such as pacing and sensitivity threshold and pacing impedance should be measured during follow‐up.…”
Section: Discussionmentioning
confidence: 99%